Water-based flash-rust-resistant salt-spray-resistant additive and preparation method thereof
By introducing modified rare earth salt solution into the water-based anti-flash rust agent to form a tight structure complex, the problem of poor temperature resistance of existing water-based anti-flash rust agents in high temperature environments is solved, and more efficient anti-flash rust and salt spray resistance is achieved.
Patent Information
- Application Number
- CN202510199526.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-24
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2045-02-24
AI Technical Summary
The existing water-based anti-flash rust agents have poor temperature resistance under high temperature environments, resulting in a decrease in anti-flash rust performance and it is difficult to effectively suppress electrochemical corrosion on metal surfaces.
A water-based anti-flash rust and salt spray resistance additive is adopted, including ethylenediaminetetramethylphosphonate sodium, N,N-dimethyldodecylamine, polydimethylsiloxane, nano-calcium carbonate and modified rare earth salt solution. The complexing reaction of the modified rare earth salt solution is used to form a tight structure complex, which enhances the anti-flash rust and salt spray resistance of the paint, and stabilizes free radicals at high temperatures and slows down the oxidation reaction.
It significantly improves the high temperature resistance and working stability of the additives, enhances the anti-flash rust and salt spray properties of the coating, and ensures that metal corrosion can still be effectively prevented under high temperature conditions.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of coating additives, and more specifically, to a water-based anti-flash rust and salt spray resistant additive and a preparation method thereof. Background Art
[0002] Water-based anti-flash rust and salt spray resistant additives are important additives developed to solve the flash rust phenomenon that occurs during the coating process of water-based coatings and to improve the durability of coatings. Flash rust is a corrosion phenomenon that occurs rapidly when metal ions are oxidized by oxygen due to the instantaneous strong electrochemical reaction between the metal substrate and the electrolyte aqueous solution in the coating during the drying process of water-based coatings. The flash rust phenomenon will seriously affect the performance of the coating, such as reducing the bonding ability of the coating with the substrate, weakening the protective performance of the paint film on the metal, and affecting the appearance. In order to combat flash rust, anti-flash rust agents came into being. Anti-flash rust agents can instantly shield metal ions or reduce the reactivity of metal ions, cut off or reduce the supply of oxygen, thereby weakening or terminating the electrochemical reaction. At the same time, the role of salt spray resistant agents is to improve the corrosion resistance and permeability resistance of the coating to resist the erosion of salt spray.
[0003] In the related art, an anti-flash rust agent for water-based anti-corrosion coatings and a preparation method thereof are disclosed in an application document with publication number CN112961525A, wherein the anti-flash rust agent includes molybdate, benzoate, benzotriazole, organic alcohol amine and deionized water. In actual use of the above-mentioned anti-flash rust agent, especially when facing a high temperature environment in chemical industry and metallurgy, the organic alcohol amine compound in the anti-flash rust agent is prone to oxidation, thereby causing the anti-flash rust agent to lose its original protective properties. In addition, under high temperature conditions, the electrochemical corrosion rate of the metal surface may accelerate, making it more difficult for the anti-flash rust agent to effectively inhibit the occurrence of corrosion. Therefore, the anti-flash rust agent in the related art has the defect of poor temperature resistance. Summary of the invention
[0004] In order to improve the temperature resistance of an anti-flash rust agent, the present application provides a water-based anti-flash rust and salt spray resistant additive and a preparation method thereof.
[0005] The present application provides a water-based anti-flash rust and salt spray resistant additive using the following technical solution: A water-based anti-flash rust and salt spray resistant additive, comprising the following raw materials in parts by weight: 50-65 parts of sodium ethylenediaminetetramethylenephosphonate; 60-70 parts of N,N-dimethyldodecylamine; 20-40 parts of polydimethylsiloxane; 20-30 parts of nano calcium carbonate; 25-40 parts of modified rare earth salt solution; 30-50 parts of deionized water; The modified rare earth salt solution is obtained by complexing 4-hydroxy-β-dihydrodamascone with a rare earth salt solution.
[0006] By adopting the above technical solution, the introduction of N,N-dimethyldodecylamine, with its unique quaternary ammonium salt structure, effectively neutralizes the acidic components in the coating system, fundamentally preventing the occurrence of flash rust. At the same time, this substance can significantly improve the corrosion resistance of the coating and provide a solid anti-corrosion barrier for the additive. The addition of sodium ethylenediaminetetramethylenephosphonate, with its strong metal surface adsorption capacity and chemical cross-linking effect, significantly accelerates the film formation speed of the coating. This feature not only further enhances the anti-flash rust performance of the coating, but also ensures that the coating forms a dense and uniform protective layer in a short time, effectively blocking the intrusion of external corrosive media, which is conducive to improving the salt spray resistance of the coating.
[0007] Rare earth salt solution itself has good corrosion resistance, which can enhance the flash rust resistance and salt spray resistance of the paint coating. Through the complexation reaction of 4-hydroxy-β-dihydrodamascone and rare earth salt solution, a complex with a tight structure is formed. This tight structure not only further enhances the salt spray resistance of the coating; but also, in a high temperature environment, organic molecules easily form free radicals and trigger chain reactions, leading to accelerated oxidation. The tight structure formed by 4-hydroxy-β-dihydrodamascone and rare earth ions may have the ability to stabilize free radicals, thereby slowing down the propagation speed of the chain reaction. Its reaction rate with oxygen is significantly reduced. This feature effectively slows down the oxidation reaction of other organic matter in the additive under high temperature conditions, thereby significantly improving the high temperature resistance of the additive.
[0008] Optionally, the modified rare earth salt solution is prepared by the following method: A. adding 4-hydroxy-β-dihydrodamascone to acetone and heating to dissolve to obtain solution A; B. Using dilute nitric acid to adjust the pH of the rare earth salt solution to 6.5-7 to obtain solution B; C. Slowly add solution B to solution A under magnetic stirring, and stir the reaction at 50-60° C. for 4-5 hours to obtain a modified rare earth salt solution.
[0009] Optionally, the volume ratio of the 4-hydroxy-β-dihydrodamascone to acetone is 1:(4-5); and the volume ratio of the solution B to the solution A in step c is 1:(0.5-0.8).
[0010] By adopting the above technical solution, the volume ratio of 4-hydroxy-β-dihydrodamascone to acetone, and the volume ratio of solution B to solution A are limited. The above reactant ratio helps to accurately control the rate of the complexation reaction while avoiding a large amount of reactant residue, thereby obtaining a modified rare earth salt solution with a tighter structure and more stable performance. The tightly structured complex can further enhance the salt spray resistance of the coating and improve the high temperature resistance of the additive.
[0011] Optionally, the rare earth salt solution is any one of Ce(NO3)3, La(NO3)3, and Pr(NO3)3.
[0012] By adopting the above technical solution, the above rare earth salt solution itself has good corrosion resistance, and can significantly enhance the flash rust resistance and salt spray resistance of the coating. Through the complex reaction, the excellent performance of the rare earth elements can be further exerted, and the overall high temperature resistance and working stability of the additive can be improved.
[0013] Optionally, the additive raw material also includes 5-10 parts of ferrous sulfate solution and 5-8 parts of zinc powder.
[0014] By adopting the above technical solution, ferrous sulfate is acidic in aqueous solution, and ferrous sulfate can be used as a regulator to adjust the pH value of the system to maintain the stability of the system. A stable pH value environment helps the sodium ethylenediaminetetramethylenephosphonate and N,N-dimethyldodecylamine in the additive to maintain component stability, preventing them from decomposing or failing due to excessively high or low pH values, thereby enhancing the overall working stability of the additive.
[0015] As an inorganic pigment and filler, zinc powder has certain chemical stability and corrosion resistance in coatings. Its presence can further enhance the physical barrier effect of the coating and reduce the direct contact of corrosive media with the metal surface, thus effectively improving the salt spray resistance of the additive.
[0016] Ferrous sulfate and zinc powder can form a weak electric field effect in the additive, which can significantly enhance the adsorption capacity of ions or molecules in the coating on the metal surface, thereby ensuring that the coating components can be tightly attached to the metal surface. Under high temperature conditions, as the temperature rises, the reaction rate of ferrous sulfate and zinc powder accelerates, and the electric field effect is enhanced, thereby effectively enhancing the adsorption capacity and film-forming efficiency of the metal surface, thereby preventing electrochemical corrosion between the metal substrate and the electrolyte aqueous solution in the coating, thereby improving the anti-flash rust performance of the additive under high temperature conditions.
[0017] Optionally, the concentration of the ferrous sulfate solution is 10%-20%.
[0018] By adopting the above technical solution, the concentration range of the above ferrous sulfate solution helps to accurately control the pH value of the system and maintain the stability of the system, thereby ensuring that other components in the additive can fully exert their performance. A stable pH environment is the key to improving the overall working stability of the additive.
[0019] Optionally, the average molecular weight of the polydimethylsiloxane is 5000-10000 Da.
[0020] By adopting the above technical solution, the polydimethylsiloxane within the above average molecular weight range helps to ensure good dispersibility and stability of the polydimethylsiloxane in the coating. As an excellent surfactant, polydimethylsiloxane can significantly improve the wettability and leveling properties of the coating, thereby helping to form a dense and uniform protective layer and improving the salt spray resistance of the coating.
[0021] Optionally, the average particle size of the nano calcium carbonate is 20-100 nm.
[0022] By adopting the above technical solution, the average particle size range of nano calcium carbonate is clarified. The average particle size of 20-100nm helps to ensure the good dispersibility and high specific surface area of nano calcium carbonate in the coating. As an excellent filler, nano calcium carbonate can significantly improve the hardness and wear resistance of the coating, while enhancing the physical barrier effect of the coating, reducing the direct contact of the corrosive medium with the metal surface, thereby improving the salt spray resistance of the coating.
[0023] The present application also provides a method for preparing a water-based anti-flash rust and salt spray resistant additive, which adopts the following technical solution: A method for preparing a water-based anti-flash rust and salt spray resistant additive comprises the following steps: S1. Mixing sodium ethylenediaminetetramethylenephosphonate, N,N-dimethyldodecylamine, a modified rare earth salt solution, a ferrous sulfate solution and deionized water at 30-50° C. and stirring for 0.5-1.5 h to obtain a preformed solution; S2. After mixing polydimethylsiloxane, nano-calcium carbonate and zinc powder with the prefabricated liquid, stirring for 0.5-1.5 hours, and then ultrasonically treating for 0.5-1.5 hours to obtain a water-based anti-flash rust and salt spray resistant additive.
[0024] In summary, this application has the following beneficial effects: 1. Since the present application adopts a modified rare earth salt solution, the rare earth salt solution itself has good corrosion resistance, thereby being able to enhance the flash rust resistance and salt spray resistance of the paint coating, and a complex with a tight structure is formed by the complexation reaction of 4-hydroxy-β-dihydrodamascone and the rare earth salt solution. This tight structure not only further enhances the salt spray resistance of the coating; moreover, in a high temperature environment, organic molecules easily form free radicals and trigger chain reactions, leading to accelerated oxidation. The tight structure formed by 4-hydroxy-β-dihydrodamascone and rare earth ions has the ability to stabilize free radicals to a certain extent, thereby slowing down the propagation speed of the chain reaction. Its reaction rate with oxygen is significantly reduced. This feature effectively slows down the oxidation reaction of other organic matter in the additive under high temperature conditions, thereby significantly improving the high temperature resistance of the additive.
[0025] 2. The raw materials of this application also include ferrous sulfate and zinc powder. Ferrous sulfate is acidic in aqueous solution. Ferrous sulfate can be used as a regulator to adjust the pH value of the system to maintain the stability of the system. A stable pH environment helps the sodium ethylenediaminetetramethylenephosphonate and N,N-dimethyldodecylamine in the additive to maintain component stability, preventing them from decomposing or failing due to excessively high or low pH values, thereby enhancing the overall working stability of the additive. Zinc powder, as an inorganic pigment and filler, has certain chemical stability and corrosion resistance in the coating. Its presence can further enhance the physical barrier effect of the coating and reduce the direct contact of the corrosive medium with the metal surface, thereby effectively improving the salt spray resistance of the additive. The weak electric field effect that can be formed by ferrous sulfate and zinc powder in the additive, the micro-electric field effect can significantly enhance the adsorption capacity of ions or molecules in the coating on the metal surface, thereby ensuring that the coating components can be closely attached to the metal surface. Under high temperature conditions, as the temperature rises, the reaction rate between ferrous sulfate and zinc powder accelerates and the electric field effect strengthens, thereby effectively enhancing the adsorption capacity and film-forming efficiency of the metal surface, thereby hindering the electrochemical corrosion between the metal substrate and the aqueous electrolyte solution in the coating, thereby improving the anti-flash rust performance of the additive under high temperature conditions. DETAILED DESCRIPTION
[0026] The present application is further described in detail below with reference to the embodiments.
[0027] Preparation Example of Modified Rare Earth Salt Solution Preparation Example 1 The modified rare earth salt solution is prepared by the following method: A. Add 1 L of 4-hydroxy-β-damascone to 4 L of acetone and heat to 45° C. to dissolve to obtain solution A; B. Use dilute nitric acid with a mass concentration of 10% to adjust the pH of Ce (NO3) 3 solution to 6.5 to obtain solution B. The initial mass concentration of Ce (NO3) 3 solution is 5%; C. Slowly add 1 L of solution B into 0.5 L of solution A under magnetic stirring, and stir the reaction at 50° C. for 4 h to obtain a modified rare earth salt solution.
[0028] Preparation Example 2 The modified rare earth salt solution is prepared by the following method: A. Add 1 L of 4-hydroxy-β-damascone to 4.5 L of acetone and heat to 45° C. to dissolve to obtain solution A; B. Use dilute nitric acid with a mass concentration of 10% to adjust the pH of Ce (NO3) 3 solution to 6.5 to obtain solution B. The initial mass concentration of Ce (NO3) 3 solution is 5%; C. Slowly add 1 L of solution B into 0.7 L of solution A under magnetic stirring, and stir the reaction at 55° C. for 4.5 h to obtain a modified rare earth salt solution.
[0029] Preparation Example 3 The modified rare earth salt solution is prepared by the following method: A. Add 1 L of 4-hydroxy-β-dihydrodamascone to 5 L of acetone and heat to 45° C. to dissolve to obtain solution A; B. Use dilute nitric acid with a mass concentration of 10% to adjust the pH of the Ce (NO3) 3 solution to 7 to obtain solution B. The initial mass concentration of the Ce (NO3) 3 solution is 5%; C. Slowly add 1 L of solution B into 0.8 L of solution A under magnetic stirring, and stir the reaction at 60° C. for 5 h to obtain a modified rare earth salt solution.
[0030] Preparation Example 4 The difference between the modified rare earth salt solution and Preparation Example 3 is that the rare earth salt solution in step b uses La(NO3)3 with a mass concentration of 5%.
[0031] Preparation Example 5 The difference between the modified rare earth salt solution and Preparation Example 3 is that the rare earth salt solution in step b uses Pr(NO3)3 with a mass concentration of 5%.
[0032] Preparation Example 6 The modified rare earth salt solution is different from Preparation Example 3 in that the 4-hydroxy-β-dihydrodamascone in step a is replaced by ethylenediaminetetraacetic acid.
[0033] Example Example 1 A water-based anti-flash rust and salt spray resistant additive, the raw material components and dosages thereof are shown in Table 1. The average molecular weight of polydimethylsiloxane is 5000Da; the average particle size of nano calcium carbonate is 20nm; and the modified rare earth salt solution is the modified rare earth salt solution prepared in Preparation Example 1.
[0034] A method for preparing a water-based anti-flash rust and salt spray resistant additive comprises the following steps: S1, mixing sodium ethylenediaminetetramethylenephosphonate, N,N-dimethyldodecylamine, modified rare earth salt solution and deionized water at 30° C. and stirring for 0.5 h to obtain a preformed solution; S2. After mixing polydimethylsiloxane, nano-calcium carbonate and the prefabricated liquid, stirring for 0.5 h, and then ultrasonically treating for 0.5 h to obtain a water-based anti-flash rust and salt spray resistant additive.
[0035] Example 2 A water-based anti-flash rust and salt spray resistant additive, the raw material components and dosages are shown in Table 1. The average molecular weight of polydimethylsiloxane is 7000Da; the average particle size of nano calcium carbonate is 60nm; and the modified rare earth salt solution is the modified rare earth salt solution prepared in Preparation Example 2.
[0036] A method for preparing a water-based anti-flash rust and salt spray resistant additive comprises the following steps: S1, mixing sodium ethylenediaminetetramethylenephosphonate, N,N-dimethyldodecylamine, a modified rare earth salt solution and deionized water at 40° C. and stirring for 1 h to obtain a preformed solution; S2. After mixing polydimethylsiloxane and nano-calcium carbonate with the prefabricated liquid, stirring for 1 hour, and then ultrasonically treating for 1 hour to obtain a water-based anti-flash rust and salt spray resistant additive.
[0037] Example 3 A water-based anti-flash rust and salt spray resistant additive, the raw material components and dosages thereof are shown in Table 1. The average molecular weight of polydimethylsiloxane is 10000 Da; the average particle size of nano calcium carbonate is 100 nm; and the modified rare earth salt solution is the modified rare earth salt solution prepared in Preparation Example 3.
[0038] A method for preparing a water-based anti-flash rust and salt spray resistant additive comprises the following steps: S1, mixing sodium ethylenediaminetetramethylenephosphonate, N,N-dimethyldodecylamine, modified rare earth salt solution and deionized water at 50° C. and stirring for 1.5 h to obtain a preformed solution; S2. After mixing polydimethylsiloxane and nano-calcium carbonate with the prefabricated liquid, stirring for 1.5 hours, and then ultrasonically treating for 1.5 hours to obtain a water-based anti-flash rust and salt spray resistant additive.
[0039] Table 1 Raw material components and amounts in Examples 1-3 (g)
[0040] Example 4 A water-based anti-flash rust and salt spray resistant additive, which is different from Example 3 in that the modified rare earth salt solution in this example is the modified rare earth salt solution prepared in Preparation Example 4.
[0041] Example 5 A water-based anti-flash rust and salt spray resistant additive is different from Example 3 in that the modified rare earth salt solution in this example is the modified rare earth salt solution prepared in Preparation Example 5.
[0042] Example 6 A water-based anti-flash rust and salt spray resistant additive, which is different from Example 3 in that the raw materials of this example also include 10g of ferrous sulfate solution with a mass concentration of 10% and 5g of zinc powder, and the average particle size of the zinc powder is 5 microns. The ferrous sulfate solution and the zinc powder are added in steps S1 and S2 respectively in the preparation method of the additive.
[0043] Example 7 A water-based anti-flash rust and salt spray resistant additive, which is different from Example 3 in that the raw materials of this example also include 7g of ferrous sulfate solution with a mass concentration of 15% and 6g of zinc powder, and the average particle size of the zinc powder is 5 microns. The ferrous sulfate solution and the zinc powder are added in steps S1 and S2 respectively in the preparation method of the additive.
[0044] Example 8 A water-based anti-flash rust and salt spray resistant additive, which is different from Example 3 in that the raw materials of this example also include 5g of ferrous sulfate solution with a mass concentration of 20% and 8g of zinc powder, and the average particle size of the zinc powder is 5 microns. The ferrous sulfate solution and the zinc powder are added in steps S1 and S2 respectively in the preparation method of the additive.
[0045] Comparative Example Comparative Example 1 The preparation scheme of water-based anti-flash rust and salt spray resistant additives for conventional coatings on the market was adopted, and 75g of ethanolamine, 20g of ammonium molybdate, 60g of ammonium benzoate and 20g of benzotriazole were added to 85g of deionized water in sequence, and stirred for 1h at room temperature to obtain the water-based anti-flash rust and salt spray resistant additive.
[0046] Comparative Example 2 A water-based anti-flash rust and salt spray resistant additive is different from Example 3 in that an equal amount of unmodified Ce (NO3) 3 solution is used in this example to replace the modified rare earth salt solution in Preparation Example 3.
[0047] Comparative Example 3 A water-based anti-flash rust and salt spray resistant additive, which is different from Example 3 in that the modified rare earth salt solution in this example is the modified rare earth salt solution prepared in Preparation Example 6.
[0048] Performance testing Test Example 1 20g of epoxy resin and 30g of water-based curing agent are placed in a vacuum-assisted planetary mixer, and the vacuum degree is maintained at -0.10MPa to obtain a water-based epoxy resin matrix; 0.5g of the water-based anti-flash rust and salt spray resistant additive of Example 1 is added to 10g of water, and ultrasonic treatment is performed for 2h, the ultrasonic power is 200W, and the ultrasonic frequency is 50kHz to obtain a dispersion; the dispersion is added to the water-based epoxy resin matrix, stirred at 200rpm for 3h, and a coating sample is obtained.
[0049] The preparation methods of the coating samples corresponding to the remaining Examples 2-8 and Comparative Examples 1-3 are the same as that of Test Example 1.
[0050] Test 1: Anti-flash rust performance test The coating samples prepared by the additives of Examples 1-8 and Comparative Examples 1-3 were respectively added 2 drops to the cold-rolled steel plate, and then the steel plate was placed in a closed environment for 120 hours to observe the degree of rust. The humidity in the closed environment was controlled by water, saturated ammonium sulfate aqueous solution and saturated sodium chloride aqueous solution, respectively. The relative humidity of the closed environment with water added was 90%, and the relative humidity of the closed environment with saturated ammonium sulfate aqueous solution added was 80%. The relative humidity of the closed environment with saturated sodium chloride aqueous solution added was 80%, and the temperature in the closed environment was 30°C. The test results are shown in Table 2.
[0051] Table 2 Anti-flash rust performance test results
[0052] Test 2: Salt spray resistance test The coating prepared in Test Example 1 was tested for salt spray resistance according to the method specified in GB / T 1771-2007 Determination of neutral salt spray resistance of paints and varnishes. The results are shown in Table 3.
[0053] Table 3 Salt spray resistance test results
[0054] Test 3: Temperature resistance test Two drops of the coating prepared in Test Example 1 were added to the cold-rolled steel plate, and then the steel plate was placed in a closed environment for 120 hours to observe the degree of rust. The humidity in the closed environment was controlled by water, saturated ammonium sulfate aqueous solution, and saturated sodium chloride aqueous solution, respectively. The relative humidity of the closed environment with water added was 90%, and the relative humidity of the closed environment with saturated ammonium sulfate aqueous solution added was 80%. The relative humidity of the closed environment with saturated sodium chloride aqueous solution added was 80%, and the temperature in the closed environment was 90°C. The test results are shown in Table 4.
[0055] Table 4 Temperature resistance test results
[0056] The anti-flash rust and salt spray resistant additives in the coatings in Examples 1-5 use a modified rare earth salt solution, which forms a tightly structured complex through the complexation reaction of 4-hydroxy-β-dihydrodamascone and rare earth ions. The tightly structured complex not only enhances the salt spray resistance of the coating, but also stabilizes free radicals at high temperatures, slows down the propagation speed of the chain reaction, and thus reduces the reaction rate of the coating with oxygen. Therefore, the coatings in Examples 1-5 can still maintain good anti-flash rust performance under high temperature conditions.
[0057] Ferrous sulfate and zinc powder are added to the anti-flash rust and salt spray resistant additives in the coatings in Examples 6-8. Since ferrous sulfate and zinc powder form a weak electric field effect in the coating, the adsorption capacity of ions or molecules in the coating on the metal surface is enhanced. At high temperatures, as the temperature rises, the reaction rate of ferrous sulfate and zinc powder accelerates, and the electric field effect is enhanced, thereby further enhancing the adsorption capacity and film-forming efficiency of the metal surface. This helps to prevent electrochemical corrosion between the metal substrate and the electrolyte aqueous solution in the coating, thereby improving the anti-flash rust performance of the coating under high temperature conditions.
[0058] The coating in Comparative Example 1 uses ingredients such as ethanolamine, ammonium molybdate, ammonium benzoate and benzotriazole, which cannot form stable free radicals or provide sufficient protective barriers to prevent metal corrosion at high temperatures. Therefore, at high temperatures, the coating of Comparative Example 1 has dark brown rust, indicating that its anti-flash rust performance under high temperature conditions is poor.
[0059] Comparative Examples 2 and 3 respectively used unmodified Ce(NO3)3 solution and ethylenediaminetetraacetic acid modified rare earth salt solution. Unmodified Ce(NO3)3 solution cannot form the same tightly structured complex as in the example, and therefore cannot provide sufficient protection to prevent metal corrosion at high temperatures. Therefore, the anti-flash rust performance of the coating of Comparative Example 2 under high temperature conditions is seriously insufficient, resulting in light brown and dark brown rust. In addition, the modified rare earth salt solution in Comparative Example 3 uses a rare earth salt solution modified with ethylenediaminetetraacetic acid. Since the complex formed by ethylenediaminetetraacetic acid and rare earth ions is not as stable as 4-hydroxy-β-dihydrodamascone, the anti-flash rust performance of the coating at high temperatures is reduced.
[0060] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A water-based anti-flash rust and salt spray resistant additive, characterized in that: The invention comprises the following raw materials in parts by weight: 50-65 parts of sodium ethylenediaminetetramethylenephosphonate; 60-70 parts of N,N-dimethyldodecylamine; 20-40 parts of polydimethylsiloxane; 20-30 parts of nano calcium carbonate; 25-40 parts of modified rare earth salt solution; 30-50 parts of deionized water; The modified rare earth salt solution is obtained by complexing 4-hydroxy-β-dihydrodamascone with a rare earth salt solution.
2. The water-based anti-flash rust and salt spray resistant additive according to claim 1, characterized in that: The modified rare earth salt solution is prepared by the following method: A. adding 4-hydroxy-β-dihydrodamascone to acetone and heating to dissolve to obtain solution A; B. Using dilute nitric acid to adjust the pH of the rare earth salt solution to 6.5-7 to obtain solution B; C. Slowly add solution B to solution A under magnetic stirring, and stir the reaction at 50-60° C. for 4-5 hours to obtain a modified rare earth salt solution.
3. The water-based anti-flash rust and salt spray resistant additive according to claim 2, characterized in that: The volume ratio of the 4-hydroxy-β-dihydrodamascone to acetone is 1:(4-5); the volume ratio of the solution B to the solution A in step c is 1:(0.5-0.8).
4. The water-based anti-flash rust and salt spray resistant additive according to claim 2, characterized in that: The rare earth salt solution is any one of Ce(NO3)3, La(NO3)3, and Pr(NO3)3.
5. The water-based anti-flash rust and salt spray resistant additive according to claim 1, characterized in that: It also includes 5-10 parts of ferrous sulfate solution and 5-8 parts of zinc powder.
6. The water-based anti-flash rust and salt spray resistant additive according to claim 5, characterized in that: The concentration of the ferrous sulfate solution is 10%-20%.
7. The water-based anti-flash rust and salt spray resistant additive according to claim 1, characterized in that: The average molecular weight of the polydimethylsiloxane is 5000-10000 Da.
8. The water-based anti-flash rust and salt spray resistant additive according to claim 1, characterized in that: The average particle size of the nano calcium carbonate is 20-100 nm.
9. A method for preparing the water-based anti-flash rust and salt spray resistant additive according to any one of claims 5 to 8, characterized in that: The steps include: S1. Mixing sodium ethylenediaminetetramethylenephosphonate, N,N-dimethyldodecylamine, a modified rare earth salt solution, a ferrous sulfate solution and deionized water at 30-50° C. and stirring for 0.5-1.5 h to obtain a preformed solution; S2. After mixing polydimethylsiloxane, nano-calcium carbonate and zinc powder with the prefabricated liquid, stirring for 0.5-1.5 hours, and then ultrasonically treating for 0.5-1.5 hours to obtain a water-based anti-flash rust and salt spray resistant additive.
Citation Information
Patent Citations
Flash rust resisting agent for water-based anticorrosive coatings, and preparation method thereof
CN112961525A
Anti-ageing rare earth modified water-based chlorosulfonated polyethylene anticorrosive paint and preparation method thereof
CN106634247A
High-temperature-resistant coating for thick coating type metal surface and preparation method of high-temperature-resistant coating
CN116162367A
Composite corrosion inhibitor as well as preparation method and application thereof
CN118028815A
Corrosion inhibition with water-soluble rare earth chelates
US5130052A
Cited By
Preparation method of chromium-free fingerprint-resistant liquid for aluminized zinc plate
CN120173465A